Estudo de Inclusões Fluidas de Jazigos de Pb-Zn-(Ag) do Centro e Nordeste de Portugal - Resultados Preliminares - C. Marques de Sá (2010)
Fluid Inclusion studies are being carried out in Pb-Zn-(Ag) deposits from NE and Central Portugal. In this brief abstract the preliminary results obtained for one of these deposits are presented: Ferronho deposit (Bragança district). Samples of quartz from the mineralized veins were petrographically studied and fluid inclusion assemblages defined in relation to different depositional events. Results from the microthermometric study provide the physical-chemical conditions under which the deposit was formed